PENGARUH PENGETAHUAN DAN KETERAMPILAN TERHADAP CAREER WELL-BEING DENGAN CAREER ADAPTABILITY SEBAGAI MEDIASI (STUDI PADA KARYAWAN GEN Z DI KOTA MALANG) - Utmiati, Nur Aulia Kusuma; Ekowati, Vivin Maharani; Alim, Syahirul (JURNAL LENTERA BISNIS, 2026)
The rapid development of the world of work accelerated by digitalization and globalization requires Generation Z to have relevant competencies and high adaptability skills. Psychological pressure, career uncertainty, and the need for new skills are major challenges for Gen Z workers in Malang City. These conditions emphasize the importance of knowledge, skills, and career adaptability in shaping career well-being. This study aims to analyze the influence of knowledge and skills on career well-being with career adaptability as a mediating variable among Generation Z employees. The study uses a quantitative approach through surveys, with data analysis using PLS-SEM to test direct and indirect relationships between concepts. The results show that knowledge and skills have a positive and significant effect on career well-being, and career adaptability is proven to mediate this relationship, so that individual competencies become more effective in improving career well-being when supported by the ability to adapt to the dynamics of the modern world of work.